Combing oxygen vacancies on TiO2 nanorod arrays with g-C3N4 nanosheets for enhancing photoelectrochemical degradation of phenol. (April 2020) - Qi, Fan; An, Weijia; Wang, Huan; Hu, Jinshan; Guo, Hongxia; Liu, Li; Cui, Wenquan
Abstract: We reported a novel TiO2-x /g-C3 N4 nanorod arrays photoelectrode by urea drop-calcined and NaBH4 reduction. Due to synergistic effect of the oxygen vacancies and the g-C3 N4 nanosheets, the TiO2-x /g-C3 N4 photoelectrode exhibited excellent photoelectrochemical property and photoelectrocatalytic activity. The photocurrent density of TiO2-x /g-C3 N4 was 6-fold and 1.5-fold higher than TiO2 and TiO2 /g-C3 N4, respectively. Meanwhile, the phenol degradation rate of TiO2-x /g-C3 N4 photoelectrodes was as high as 83% under the stimulated solar light. Besides, the oxygen vacancies could promote the formation of the Z-scheme heterojunction between the TiO2 nanorods and g-C3 N4 nanosheets.